Hubungan Faktor Individu Dan Lingkungan Sosial Dengan Partisipasi Masyarakat Dalam Pengelolaan Sampah Rumah Tangga (Kasus Kampung Sengked, RT 03/RW 03 Desa Babakan Kecamatan Dramaga, Kabupaten Bogor) - Mujiburrahmad Mujiburrahmad; Firmansyah Firmansyah (Jurnal Agrisep, 2014)
Abstrack. One cause of the large amounts of waste due to waste generated per day is not comparable with the level of service performed, one due to limited human resources of the Department of Housing and Settlements in West Java province. The aim of the research are: (1) to analyze the level of community participation in the process of household waste and (2) analyze the relationship between individual factors and social environment with the level of community participation in the management of household waste. The research was conducted in the village Sengked, precisely at RT 03 / RW 03 Desa Babakan subdistrict, Bogor regency Dramaga. This study uses the type of explanation (explanatory), data analysis using quantitative descriptive methods. To determine the factors associated with the participation of members of a group of women farmers used the Spearman rank correlation test (rs). Results of the study: (1) The level of citizen participation in the management of household waste in the planning and implementation stages are categorized as moderate, while participation in the deployment phase or enjoy the fruits are categorized as high, (2) participation in planning include: interest / interest of the respondents, non-formal education, skill sorting garbage, manure making skills, the skills to make handicrafts from plastic waste, leisure, knowing the activities and norms / regulations on the environment, (3) Participation in the implementation include: interest / interest of respondents, non-formal education , waste sorting skills, skills to make fertilizer, skills make handicrafts from plastic waste, leisure, knowing the activities and norms / regulations on the environment and (4) Participation in the utilization of the results include: interest / interest of respondents, formal and non-formal, waste sorting skills, the skills to make fertilizer, and free time.